2019
DOI: 10.1039/c9ra06000f
|View full text |Cite
|
Sign up to set email alerts
|

Natural rubber latex foam with particulate fillers for carbon dioxide adsorption and regeneration

Abstract: To reduce the carbon dioxide (CO 2 ) concentration in the atmosphere, natural rubber (NR) was developed as a rubber foam for CO 2 adsorption. Although the CO 2 adsorption capacity of the NR latex foam produced by mixing with a cake mixer (CM) was higher than that produced with an overhead stirrer (OS), both capacity values were still low. To improve the CO 2 adsorption capacity, the use of unmodified and (3-aminopropyl) triethoxysilane-modified silica particles as fillers in the CM rubber foam matrix was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The MC concentration had an obvious effect on the absorption level and the optimum MC concentration was 2% generating the highest adsorption capacities for some organic solvents. In another work, Panploo and coworkers developed an eco-friendly NR latex foam to adsorb CO 2 gas under environmental temperature and pressure [ 302 ]. They used two different methods including overhead stirrer (OS) or cake mixer (CM) to produced NR latex foams.…”
Section: Applications Of Rubber Foamsmentioning
confidence: 99%
“…The MC concentration had an obvious effect on the absorption level and the optimum MC concentration was 2% generating the highest adsorption capacities for some organic solvents. In another work, Panploo and coworkers developed an eco-friendly NR latex foam to adsorb CO 2 gas under environmental temperature and pressure [ 302 ]. They used two different methods including overhead stirrer (OS) or cake mixer (CM) to produced NR latex foams.…”
Section: Applications Of Rubber Foamsmentioning
confidence: 99%
“…New applications of the NR latex foam rubbers allow their use as absorbent materials for oils and carbon dioxide (CO 2 ). NR latex foam rubber filled with silica can serve as a CO 2 absorbing material [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 . We found that all the foam samples exhibited the open–cell structure with heterogeneous sizes of bubble (heterogeneous pore size), a known effect of the Dunlop process 34 , 35 . However, the amount of NR matrix present affects the morphological properties of the foam samples.…”
Section: Resultsmentioning
confidence: 86%